2012
DOI: 10.1093/jxb/ers189
|View full text |Cite
|
Sign up to set email alerts
|

PrCYP707A1, an ABA catabolic gene, is a key component of Phelipanche ramosa seed germination in response to the strigolactone analogue GR24

Abstract: After a conditioning period, seed dormancy in obligate root parasitic plants is released by a chemical stimulus secreted by the roots of host plants. Using Phelipanche ramosa as the model, experiments conducted in this study showed that seeds require a conditioning period of at least 4 d to be receptive to the synthetic germination stimulant GR24. A cDNA-AFLP procedure on seeds revealed 58 transcript-derived fragments (TDFs) whose expression pattern changed upon GR24 treatment. Among the isolated TDFs, two up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 50 publications
6
84
2
Order By: Relevance
“…The application of the synthetic strigolactone GR24 to seeds of the parasitic plant Phelipanche ramosa resulted in elevated expression of a gene encoding an ABA catabolic enzyme and decreased accumulation of ABA (Lechat et al, 2012). Similar results were obtained in thermoinhibited Arabidopsis seeds and in Striga hermonthica (Toh et al, 2012).…”
Section: Aba Acts Downstream or Independently Of Brc1supporting
confidence: 60%
“…The application of the synthetic strigolactone GR24 to seeds of the parasitic plant Phelipanche ramosa resulted in elevated expression of a gene encoding an ABA catabolic enzyme and decreased accumulation of ABA (Lechat et al, 2012). Similar results were obtained in thermoinhibited Arabidopsis seeds and in Striga hermonthica (Toh et al, 2012).…”
Section: Aba Acts Downstream or Independently Of Brc1supporting
confidence: 60%
“…9.3c; see Sect. 9.2.1) and Lechat et al (2012) showed significant up-regulation of the ABA catabolism gene, PrCYP707A1, after stimulating conditioned P. ramosa seeds with GR24 ( Fig. 9.8b; see Sect.…”
Section: Relief Of Primary Dormancymentioning
confidence: 93%
“…Usually considered as an undifferentiated body, recent works indicated that two distinct regions may be present in the embryo of P. aegyptiaca (Joel et al, 2011). It is suggested that the two perisperm cells located between the embryo and the micropyle may contain the putative receptors of germination stimulants (GSs) (Lechat et al, 2012). The Orobanche tiny seeds may easily spread to other fields and can persist in soil for decades (Prider et al, 2013), leading to an accelerated increase of contamination in the infested areas in which susceptible crops might be affected.…”
Section: The Seedsmentioning
confidence: 99%